Why Is Strategic Purchasing Critical for Universal Health Coverage in Sub-Saharan Africa?. Issue 2 (1st March 2022) - Gatome-Munyua, Agnes; Sieleunou, Isidore; Sory, Orokia; Cashin, Cheryl
ABSTRACT: To make progress toward universal health coverage (UHC), most countries need to commit more public resources to health. However, countries can also make progress by using available resources more effectively. Health purchasing, one of the health financing functions of health systems, is the transfer of pooled funds to health providers to deliver covered services. Purchasers can be either passive or strategic in how they transfer these funds. Strategic purchasing is deliberately directing health funds to priority populations, interventions, and services, and actively creating incentives so funds are used by providers equitably and aligned with population health needs. Strategic purchasing is particularly important for countries in sub-Saharan Africa because public funding for health has often not kept pace with UHC commitments. In addition, there is wide variation in progress toward UHC targets and health outcomes on the continent that does not always correlate with per capita government health spending. This paper explores the critical role strategic purchasing can play in the movement toward UHC in sub-Saharan Africa. It explores the rationale for strategic purchasing and makes the case for a more concerted effort by governments, and the partners that support them, to focus on and invest in improving strategic purchasing as part of advancing their UHC agendas. The paper also discusses the promise of strategic purchasing and the challenges of realizing this promise in sub-Saharan Africa, and it provides options for practical steps countries can take to incrementally improve strategic purchasing functions and policies over time.